2022
DOI: 10.48550/arxiv.2202.08813
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slip competition and rotation suppression in tantalum and copper during dynamic uniaxial compression

Abstract: When compressed, a metallic specimen will generally experience changes to its crystallographic texture due to plasticity-induced rotation. Ultrafast x-ray diffraction techniques make it possible to measure rotation of this kind in targets dynamically compressed over nanosecond timescales to the kind of pressures ordinarily encountered in planetary interiors. The axis and the extent of the local rotation can provide hints as to the combination of plasticity mechanisms activated by the rapid uniaxial compression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 67 publications
0
1
0
Order By: Relevance
“…In previous laser-plasma shock experiments that viewed rotation in single crystals 175 the Taylor model was used 166 , where line elements perpendicular to the compression access are conserved. However, it can easily be shown that the situation is more complex for single slip when the deformation of the crystal takes place under the boundary conditions of uniaxial compression, and Heighway and Wark have shown that neither of these classic models correctly predicts the degree of rotation for a single crystal subject to uniaxial compression and undergoing single slip 176 ; furthermore, there is good evidence from MD simulations that multiple slip systems are active in these experiments 177 . Of course, in real polycrystalline materials, such as those observed in the Wehrenberg experiments, whilst the condition of uniaxial strain must hold globally, it need not hold locally owing to grain-grain interactions 178 .…”
Section: B Strength and Plasticitymentioning
confidence: 99%
“…In previous laser-plasma shock experiments that viewed rotation in single crystals 175 the Taylor model was used 166 , where line elements perpendicular to the compression access are conserved. However, it can easily be shown that the situation is more complex for single slip when the deformation of the crystal takes place under the boundary conditions of uniaxial compression, and Heighway and Wark have shown that neither of these classic models correctly predicts the degree of rotation for a single crystal subject to uniaxial compression and undergoing single slip 176 ; furthermore, there is good evidence from MD simulations that multiple slip systems are active in these experiments 177 . Of course, in real polycrystalline materials, such as those observed in the Wehrenberg experiments, whilst the condition of uniaxial strain must hold globally, it need not hold locally owing to grain-grain interactions 178 .…”
Section: B Strength and Plasticitymentioning
confidence: 99%